2017
DOI: 10.1111/iej.12731
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic treatment‐related antibiotic prescribing patterns of South African oral health professionals

Abstract: The frequency of antibiotic prescribing by South African dental practitioners for patients undergoing endodontic treatment is relatively low and predominantly involved narrow spectrum antibiotics. It, however, remains important that antibiotics are only prescribed when clinically essential, such as when there are obvious systemic effects. These include fever above 37 degrees, malaise, lymphadenopathy, trismus, increase swelling, cellulitis, osteomyelitis and persistent infection. The wider dissemination and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In this study, 75% of practitioners prescribed amoxicillin combined with clavulanic acid, while in Spain 5 it was the antibiotic most prescribed by dentists (61%). In South Africa 7 , amoxicillin is also the antibiotic of choice for endodontic infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 75% of practitioners prescribed amoxicillin combined with clavulanic acid, while in Spain 5 it was the antibiotic most prescribed by dentists (61%). In South Africa 7 , amoxicillin is also the antibiotic of choice for endodontic infections.…”
Section: Discussionmentioning
confidence: 99%
“…1. Have a doctorate in dental surgery and be regularly enrolled in either A self-administered questionnaire based on models from previous studies [6][7][8][9][10] was used. It is presented in the form of a questionnaire and meets a number of criteria, such as the use of closed questions as much as possible, the use of a clear universal vocabulary, and the use of short, simple questions, without negation and developing only one idea.…”
Section: Methodsmentioning
confidence: 99%
“…The American Association of Endodontists (AAE) has recommended using amoxicillin with or without metronidazole for patients who do not have hypersensitivity to penicillin, and they recommend clindamycin for patients with hypersensitivity to penicillin ( 6 ). Most practitioners prescribe narrow-spectrum antibiotics to manage endodontic infections ( 5 , 7 , 8 ). However, in some countries, many dental practitioners have preferred broad-spectrum antibiotics instead of prescribing a narrow-spectrum antibiotic ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that antibiotics have been prescribed for 10% of endodontic cases ( 7 ). Numerous investigations have focused on antibiotic prescription patterns in different regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is not unique. While it might appear that dental practitioners are prescribing antibiotics judiciously in South Africa, according to Lalloo et al, there was no consensus amongst these practitioners on when and why to prescribe antibiotics for dental use (Lalloo et al 2017a ). The implications of these findings are that there could be inconsistencies in antibiotic prescription trends for dental use (Ncube et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%